Population Change and Population Health: A Spatio-temporal Analysis of New Brunswick Communities - Peters, Paul (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2017)
This paper considers population change in small areas of New Brunswick in relation to community-level population health indicators. Population forecasts developed via regionally constrained models are presented in conjunction with health indicators data for health zones and health council communities. Temporal and spatial variation in health indicators is discussed in relation to where population growth is forecasted to occur, and where there will be continued population decline. The results show that population growth is forecasted only for the areas surrounding Fredericton, Moncton, and Saint John, with most other areas predicted to experience continued population decline, even if the province as a whole does not. These forecasts are within a context where communities with declining population are also those with lower values across a range of non-medical determinants of health. These results present an opportunity to focus provincial strategies based on the combination of observed trends of population change and geographic inequalities of population health.